Ellipsometric Study of the Zinc Selenide Natural Cleaves Oxidation - Оdarych V. А. (Physics and Chemistry of Solid State, 2015)
Measuring of ellipsometric parameters of the light reflected from the fresh cleaves surface of zinc selenide are conducted under atmospheric conditions during one year. It has been found that the process of cleaves surface interaction with air consists of two stages. A layer with thickness to 7 nm is formed on the first stage within to 3 weeks. This layer optical constants are a little less than zinc selenide optical constants. An external transparent layer with the index of refraction approximately 1,4 and thickness to 2,5 nm show itself on the second stage from one month of to year. Supposed, this external layer contains the mixture of an unstable oxides and air.